2016
DOI: 10.17549/gbfr.2016.21.2.20
|View full text |Cite
|
Sign up to set email alerts
|

The Green Brand Marketing Strategies that Utilize Word of Mouth : Survey on Green Electronic Products in Indonesia

Abstract: In this study, the objective is focused to explain the relationship between the three independent variables (price fairness, green brand quality and green risk) and Words of Mouth (WOM), which is mediated by the satisfaction and trust. Sample is taken as many as 200 visitors at the Mall in Surakarta -Indonesia, who had the intention to buy liquid edge display (LED) screen TV. Of all the questionnaires returned, there are 12 questionnaires that cannot be used. By using Generalized Structured Component Analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
(90 reference statements)
1
9
0
Order By: Relevance
“…Previously validated measurement items were adapted to the context of this study. Table 1 presents how existing studies such as those by Martínez (2015), Taufique et al (2017), Mohd Suki (2016, Tsai (2014), Haryanto andBudiman (2016) and Yadav and Pathak (2017), which were adapted to measure the constructs in this study. The measures were operationalised with a five-point Likert scale.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously validated measurement items were adapted to the context of this study. Table 1 presents how existing studies such as those by Martínez (2015), Taufique et al (2017), Mohd Suki (2016, Tsai (2014), Haryanto andBudiman (2016) and Yadav and Pathak (2017), which were adapted to measure the constructs in this study. The measures were operationalised with a five-point Likert scale.…”
Section: Methodsmentioning
confidence: 99%
“…The purchase of energy-efficient products involves a situation in which the buyer cannot ascertain the credibility of the environmental attributes of a product claimed by the seller (Atkinson and Rosenthal, 2014;Chen et al, 2019). The price and quality of the product have been identified as two relevant signals that can affect customer trust towards pro-environmental products (Chen and Chang, 2013;Marakanon and Panjakajornsak, 2017;Mulcahy et al, 2015;Haryanto and Budiman, 2016).…”
Section: Marketing Signals: Perceived Product Quality and Product Pricementioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Morgan and Hunt (1994), it was found that trust and commitment are major factors in deriving successful relationships between sellers and buyers (consumers) and that commitment, which is a concept similar to loyalty, is, in fact, a leading variable of loyalty. Moreover, Haryanto and Budiman (2016) claims that trust is a main factor in drawing the loyalty of customers at a shopping mall. To examine the relationship between trust and loyalty, many studies assert that trust in a salesperson is a determinant factor of loyalty and that it has a positive effect on consumers' behavioral loyalty (Chaudhuri and Holbrook, 2001;Kwon, Kim, and Lee, 2003;Sirdeshmukh, Singh, and Sabol, 2002;Taylor and Hunter, 2003).…”
Section: Relationship Between Trust and Loyalty (Wom)mentioning
confidence: 99%
“…Frequently that price is used as predictor of quality, that is if the price of a brand is high, the quality of that brand is also high, this is also called the reasonableness of price. In the behavioral process, price fairness is conceptually positively related to purchasing decisions, meaning the higher the fairness of the price, the higher the decision to buy against the product (Campbell 1999, Vaidyanathan & Aggarwal 2003, Xia et al 2004, Haryanto & Budiman 2016.…”
Section: Introductionmentioning
confidence: 99%